Effect of dietary simvastatin and L-carnitine supplementation on blood biochemical parameters, carcass characteristics and growth of broiler chickens - Panahi, H.; Bouyeh, M.; Behzadpour, D.; Seidavi, A.; SimÃµes, J.; Tufarelli, Vincenzo; Staffa, V.N.; Tinelli, A.; Ayasan, T.; Laudadio, V. (Journal of the Indonesian Tropical Animal Agriculture, 2019)
The aim of this study was to evaluate the effect of simvastatin (SIM) and L-carnitine (LC) additives and their interactions, on productive performance and carcass quality of broilers. For this purpose, a feeding trial was conducted, under 3×3 factorial design, using SIM at 0, 1 or 2 g/kg level and LC at 0, 150 or 300 mg/kg level in a basal-diet and originating a total of nine treatments: T1 (control-diet, 0/0), T2 (0/150), T3 (0/300), T4 (1/0), T5(1/150), T6 (1/300), T7 (2/0), T8 (2/150), and T9 (2/300). Feed intake was higher in T2 (4716 g), T7 (4722 g) and T9 (4698 g) than in T1 (4545 g; P<0.05) considering the last growing phase (35-42 days) or whole 42-day production cycle. An improvement of feed efficiency was also observed in T8 (1.64) and T9 (1.67) when compared to T1 (1.77; P<0.05), and these were mainly due to SIM × LC interactions (P<0.05). The LC influenced positively (P<0.05) the weight of eviscerated carcass, breast, drumsticks and abdominal fat, as well as plasma triglycerides level. This findings suggests that the combination of SIM and LC additives have a positive influence on growth performance and carcass traits of broiler chickens.